Heterologous artificial insemination: the conflict between the right to recognition of genetic origin and donor intimacy (Research, Society and Development, 2022)
The present article sought to discuss how the Brazilian legal system sees the conflict between the recognition of genetic origin and the intimacy of the gamete donor and the future weight of the heterologous artificial insemination technique in the life of the individual generated from it, since it does not there is normalization in addition to the subjective concepts applied to each case. Therefore, the work was based on a qualitative study developed through bibliographic research, analyzing the relevant themes that permeate the theme, namely: family planning, sexual and reproductive rights, among others. Considering also the constitutional perspective and the conflicts of constitutional norms of the right to intimacy and identity, which have been placed on opposite sides, when in fact they are species that derive from the right to personality. The general objective was to analyze the best way to solve the antagonism of the theme, that is, the right to recognition of genetic origin and the right to identity and intimacy of the donor. It was shown that the best way to resolve the impasse is from the principled weighting of the norms, as in the Brazilian legal system there is no hierarchy between constitutional principles, whether explicit or implicit, as well as, there is no regulatory law, thus, to find out what the outlines of the fundamental rights and the identity of the donor and the individual are more than necessary as a matter of law there is a democratic and reassuring state that seeks the dignity of the human person on both sides.